Depressive Symptom and Associated Factors Among School Adolescents of Urban, Semi-Urban and Rural Areas in Bangladesh: A Scenario Prior to COVID-19 - Anjum, Afifa; Hossain, Sahadat; Hasan, M. Tasdik; Alin, Sayma Islam; Uddin, Md. Elias; Sikder, Md. Tajuddin (Frontiers in Psychiatry, 2021)
Background: The purpose of this study was to investigate the prevalence of depressive symptom and the factors associated with this condition among urban, semi-urban and rural adolescents in the Dhaka district of Bangladesh. Methods: A cross sectional study using two stage cluster sampling procedure was performed. A self-administered questionnaire was conveyed to 2355 adolescents from nine secondary schools of Dhaka district of Bangladesh. Of the respondents, 2313 completed the nine item Patient Health Questionnaire (PHQ-9). Besides, sociodemographic information, self-reported body image as well as modification of Leisure Time Exercise Questionnaire (LTEQ) and WHO Global PA Questionnaire (GPAQ) were used to determine the sociodemographic and lifestyle factors associated with depressive symptom among adolescents. Results: A total of 30.1% adolescents were found to be suffering from moderate to severely severe depressive symptom. Females (60.8%) were found suffering significantly more than males (39.2%). Sociodemographic factors, for example, residential setting and family size were found significantly associated with depressive symptom among adolescents. Adjusted estimate of logistic regression shows that physical inactivity (AOR: 1.44; 95% CI: 1.14-1.84), >2 hours/day screen time (AOR: 1.68; 95% CI: 1.39-2.03), sleep dissatisfaction (AOR: 3.23; 95% CI: 2.64-3.96), and underweight body image perception (AOR: 2.30; 95% CI: 1.70-3.13) were significantly associated with depressive symptom among adolescents. Conclusions: Among urban, semi-urban and rural school adolescents in Dhaka, Bangladesh, depressive symptom is quite prevalent. To lessen the spread of depressive symptom among Bangladeshi adolescents, urgent steps should therefore be taken.